2007
DOI: 10.1152/ajpcell.00137.2006
|View full text |Cite
|
Sign up to set email alerts
|

MKP-1 switches arginine metabolism from nitric oxide synthase to arginase following endotoxin challenge

Abstract: L-Arginine (L-arg) is metabolized to nitric oxide (NO) by inducible NO synthase (iNOS) or to urea and L-ornithine (L-orn) by arginase. NO is involved in the inflammatory response, whereas arginase is the first step in polyamine and proline synthesis necessary for tissue repair and wound healing. Mitogen-activated protein kinases (MAPK) mediate LPS-induced iNOS expression, and MAPK phosphatase-1 (MKP-1) plays a crucial role in limiting MAPK signaling in macrophages. We hypothesized that MKP-1, by attenuating iN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 37 publications
3
64
1
Order By: Relevance
“…Recent studies revealed that Mkp-1-deficient mice have inducible nitric oxide synthase-mediated hypotension when challenged with low doses of endotoxin (3). In correlative studies, MKP-1 was shown to be important in switching arginine metabolism from nitric oxide synthase to arginase following LPS challenge of peritoneal macrophages derived from WT or Mkp-1 null mice (36). Other investigators reported increased mortality in Mkp-1 null mice challenged with Gram-positive bacterial infection, through the inactivation of JNK and p38 (56).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that Mkp-1-deficient mice have inducible nitric oxide synthase-mediated hypotension when challenged with low doses of endotoxin (3). In correlative studies, MKP-1 was shown to be important in switching arginine metabolism from nitric oxide synthase to arginase following LPS challenge of peritoneal macrophages derived from WT or Mkp-1 null mice (36). Other investigators reported increased mortality in Mkp-1 null mice challenged with Gram-positive bacterial infection, through the inactivation of JNK and p38 (56).…”
Section: Discussionmentioning
confidence: 99%
“…MKP-1 wild-type and KO mice were kindly provided by Yusen Liu (The Research Institute at Nationwide Children's Hospital, Columbus, OH) (42). Female LDL-R −/− mice (B6.129S7-Ldlr tmIHer /J) were obtained from Jackson Laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…The activation and expression of endothelial arginase II can also be induced by a variety of vascular stimulants, including OxLDL, LPS, TNF-α, IFN-γ, 8-bromocGMP, and hypoxia [7,10,[12][13][14]. Arginase activation/upregulation results in arginase/NOS imbalance, as well as de-creased NO production, and has been demonstrated to contribute to endothelial dysfunction, in a number of diseases/ pathophysiological processes, including aging [4], diabetes [15][16][17], hypertension [18][19][20], and atherosclerosis [14,21].…”
Section: Introductionmentioning
confidence: 99%